2011
DOI: 10.1111/j.1582-4934.2011.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical genetics and epigenetics of telomerase

Abstract: Telomerase is a specialized reverse transcriptase that extends and maintains the terminal ends of chromosomes, or telomeres. Since its discovery in 1985 by Nobel Laureates Elizabeth Blackburn and Carol Greider, thousands of articles have emerged detailing its significance in telomere function and cell survival. This review provides a current assessment on the importance of telomerase regulation and relates it in terms of medical genetics. In this review, we discuss the recent findings on telomerase regulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 105 publications
0
28
0
Order By: Relevance
“…This especially important in germinal cells in which it is necessary to keep a normal telomeric length after many cellular divisions. Important contributions about the epigenetic control of telomeres have been reported recently (Koziel et al, 2011). In that way, Maria Blasco has suggested that telomeres are under epigenetic control (García-Cao et al, 2004).…”
Section: Regulation Of Telomerase Activity By Glutathionementioning
confidence: 99%
“…This especially important in germinal cells in which it is necessary to keep a normal telomeric length after many cellular divisions. Important contributions about the epigenetic control of telomeres have been reported recently (Koziel et al, 2011). In that way, Maria Blasco has suggested that telomeres are under epigenetic control (García-Cao et al, 2004).…”
Section: Regulation Of Telomerase Activity By Glutathionementioning
confidence: 99%
“…[3][4][5][6][7][8][12][13][14][15] In recent times, interests are rising to dissect out the contribution of DNA methylation, histone methylation, histone acetylation, and also non-coding RNAs in the epigenetically facilitated expression of hTERT. [25][26][27][28][31][32][33]44 Telomerase activity was detected in more than 95% of advanced stage breast cancers. It was absent in 19%-32% of less advanced cancers.…”
Section: Awakening and Activation Of Telomerase In Carcinomamentioning
confidence: 99%
“…75,88 Clinical relevance of epigenetic regulation of TERT In recent times, numerous reports are available to support several molecular inhibitors and phytochemical agents that block epigenetic modifiers such as DNMTs and HDACs, and as a consequence, the activity and expression of TERT are blocked. [25][26][27][28][29][30][31][32][33][89][90][91][92] In spite of several in vitro and in vivo studies pinpointing the concomitant use of several epigenetic inhibitors and telomerase inhibitors, the success is awaited in the form of clinical trial attempts and outcomes. However, certain clinical success in the form of small-molecule inhibitor drugs targeting DNA methylation (e.g.…”
Section: Epigenetic Inhibitors To Telomerase Therapeutic Quenchingmentioning
confidence: 99%
“…Understanding how telomerase is regulated will also lead to improved targeting of telomerase as a therapy for genetic diseases and cancer (32).…”
Section: Telomerase Inhibitionmentioning
confidence: 99%
“…Human Telomerase Reverse Transcriptase has recently been shown to be affected by MicroRNAs (32). The MicroRNAs, also known as miRNAs or miRs, are noncoding, single stranded RNAs that have recently been shown to play important roles in many biological processes such as development, differentiation, apoptosis and proliferation (33).…”
Section: Targeting Human Telomerase Reverse Transcriptase and Human Tmentioning
confidence: 99%